Sistem Informasi Main Parts Gas Turbine Berbasis Intranet Pada PT. Indonesia Power Unit Bisnis Pembangkit Priok - Liu, Yefrie MC (Jurnal Informatika dan Komputasi STMIK Indonesia Jakarta, 2012)
Gas turbine maintenance costs are relatively high so that the term is "Recondition parts" or "Refurbish parts". To obtain the optimum maintenance costs, spares usage should be maximized to recondition spare parts reached the age limit. To maximize the use of reconditioned parts, needs accurate data on the "tour of duty" and the life of Equivalent Operating Hour (EOH) for "every single piece". Recording of data "every single piece" can be done well and is useful if stored in a data base which can be accessed web-based. The benefits of web-based data base application is to assist in making planning program as outlined in the work plan budget, so that the resulting cost of maintaining the optimum. Kata kunci: a web database, gas turbines, the cost of maintenance, spare parts reconditioning